2021
DOI: 10.1155/2021/8891298
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Artificial and Nonartificial Intelligence in the New Product Success with Moderating Role of New Product Innovation: A Case of Manufacturing Companies in China

Abstract: Currently, there is an increasing trend in the organizations towards examining the artificial intelligence and nonartificial intelligence for the innovation and success of the new product, as well as getting the intentions of the upcoming researchers. Thus, the purpose of the ongoing study is to examine the role of artificial and nonartificial intelligence in the new product success along with the moderating role of new product innovation in the manufacturing organizations of China. The quantitative methods ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…Education has long been associated with pro-environmental attitudes and behaviours (Huo et al, 2021a ), and both were related to green consumerism. Recent research on the higher level of education has suggested more pro-environmental attitudes and behaviour towards greenhouse effect products (Jianjun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Education has long been associated with pro-environmental attitudes and behaviours (Huo et al, 2021a ), and both were related to green consumerism. Recent research on the higher level of education has suggested more pro-environmental attitudes and behaviour towards greenhouse effect products (Jianjun et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…All the local and multinational marketers are fighting and competing to attain and retain their valuable customers to achieve their sales targets (Huo et al, 2021a ). These technological platforms have enhanced awareness of different available options and made the competition more intense and focused (Jianjun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…IT operation enables the firm to use information technology to manage the market, customer information, new product launching, and product quality and customer retention (Jianjun et al, 2021). In sense, IT operation requires technical skills such as decisionmaking, effective problem solving, and managerial skills.…”
Section: Research Model and Hypotheses Development 21 It-competencies And Organizational Performancementioning
confidence: 99%
“…Winatapradja (2013), also claims that the brand awareness has a serious and considerable supremacy on the decision to repurchase products. Research from Sari and Santika (2017) also stated that in the Denpasar region the brand name or tag marks of ASUS smartphone products appreciation has a crucial impact (Jianjun et al, 2021). Research from Astawa and Rahanatha (2021);Surianto, Setiawan, Sumiati, and Sudjatno (2020) and Razak (2019) also stated that repurchase objectives are being highly or majorly impacted by brands or trademarks.…”
Section: Introductionmentioning
confidence: 99%